Review of We Dream Together; Dominican Independence, Haiti and the Fight for Caribbean Freedom - Martínez, Samuel (European Review of Latin American and Caribbean Studies, 2019)
We Dream Together; Dominican Independence, Haiti and the Fight for Caribbean Freedom, by Anne Eller. Duke University Press, 2017